A Critical Analysis of Digital Tools Among The Visual Artists - Kalaiselvan, S; Kalimuthu, A; Kumar, B. Senthil (International Journal of Computer Sciences and Engineering, 2018)
The aim of the research paper is to study the impact of digital tools among the visual artists. Due to the fast changes in the information and communication technology tools, the digital tools develops and changes day by day. Lack of proper training related to software and tools affects the visual artists with the age groups 35 to 45. The traditional way of doing visual works requires special skills such as eye, hand and mind coordination. Working in the digital system needs other skills such as technical, digital and software knowledge. Even though the pre-production, production and post-production process simplified, it develops a pressure among the traditional visual artist to change their perspective and view of the fine arts. Updating the software version and the new digital tools’ related knowledge makes them depend on the software and technical system rather than the free expression and creativity. Particularly, the artists between the age groups 35 to 45 favor the concept of creating visuals by using brushes and other traditional media. Working with the system develops a stress among the artists. Many of the above age groups give feedback which does not favor the concept of digital graphics. A digital tool gives more flexibility in all the stages of graphic design, drawing & painting, 2D, and 3D animation process. Furthermore, it reduces the complexity of the process of editing, retouching, storing, printing, copying and developing, etc. Working with computer the system for long hours is difficult for the visual artists of age groups 35 to 45. Many artists express their views in favor due to the medium and comfort was given by the traditional brushes and other materials. Handling keyboard and mouse requires more muscular movements than the application of brushes.